Efficacy and Acceptability of Intermittent Aerobic Exercise on Polysomnography‐Measured Sleep in People With Rheumatoid Arthritis With Self‐Reported Sleep Disturbance: A Randomized Controlled Trial. Issue 5 (28th January 2022) - Loeppenthin, Katrine; Esbensen, Bente Appel; Klausen, Julie Midtgaard; Østergaard, Mikkel; Christensen, Jesper Frank; Tolver, Anders; Thomsen, Tanja; Bech, Julie Schjerbech; Jennum, Poul
Abstract : Objective: This study's objective was to investigate the efficacy and acceptability of intermittent aerobic exercise training on sleep parameters, fatigue, pain, depressive symptoms, physical function, and cardiorespiratory fitness in people with rheumatoid arthritis (RA). Methods: Thirty‐eight people with RA were assigned to intermittent aerobic exercise training (three sessions/week for 6 weeks; intervention group, n = 17) or usual care (control group, n = 21). The primary outcome was a change in polysomnography‐assessed sleep efficiency from baseline to the end of the intervention. Secondary outcomes were sleep quality (Pittsburgh Sleep Quality Index), fatigue (Bristol Rheumatoid Arthritis Fatigue Multi‐Dimensional Questionnaire), depression (Center for Epidemiological Studies‐Depression), and cardiorespiratory fitness (watt max test). Results: No between‐group differences were found in changes in polysomnography‐assessed sleep efficiency (0.04; 95% confidence interval [CI]: −0.02 to 0.09, P = 0.17). In the intervention group, sleep efficiency was improved significantly from baseline (0.84; 95% CI: 0.80‐0.88) compared with the end of the intervention (6 weeks) (0.88; 95% CI: 0.85‐0.92); however, there was no significant difference in the control group. Fatigue and depression measures were significantly lower in the intervention group than in the control group. Between‐group differences were overall fatigue (−16.1; 95% CI: −25.1 to −7.0, P = 0.001), physical fatigue (−5.0; 95% CI: −7.3 to −2.7, P = 0.0001), cognitive fatigue (−2.4; 95% CI: −4.2 to 0.6, P = 0.009), living with fatigue (−2.5; 95% CI: −4.5 to −0.5, P = 0.01), and depressive symptoms (−6.8; 95% CI: −12.4 to −1.1, P = 0.02). Conclusion: The intervention yielded no significantly better sleep efficiency compared with usual care. However, aspects of fatigue, including physical and cognitive fatigue, and depressive symptoms were significantly improved in the intervention group.